Mechanical Properties Analysis of Aluminum Alloy with Heat Treatment Variation - Prabowo, Dimas Aditya; Dewanti, Rina Kusuma (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
Heat treatment plays a critical role in controlling the mechanical performance of aluminum alloys used in structural, automotive, and aerospace applications. Variations in solution treatment, aging temperature, holding time, and cooling rate significantly influence strength, hardness, and ductility. This study aims to analyze the mechanical properties of aluminum alloys under different heat treatment conditions through a systematic synthesis of experimental findings reported in recent peer reviewed literature. The research applies a qualitative comparative method by examining tensile strength, hardness, fatigue resistance, and microstructural evolution across multiple aluminum alloy series, including 6xxx, 7xxx, and Al-Si based alloys. The results indicate that optimized heat treatment parameters consistently enhance mechanical properties, with tensile strength improvements ranging from 20 percent to over 50 percent depending on alloy composition and treatment route. Excessive aging or improper quenching, however, leads to strength degradation and reduced ductility. Comparative analysis confirms that precipitation hardening and controlled grain refinement are the dominant mechanisms governing performance improvement. This study provides a consolidated technical reference for selecting heat treatment parameters to achieve targeted mechanical properties in aluminum alloys and supports process optimization in industrial manufacturing.